COMPARATIVE EVALUATION OF MYOCARDIAL REMODELING IN PATIENTS WITH HYPERTENSIVE DISEASE AND COMORBIDITY WITH CORONARY HEART DISEASE - Kuzminova, N.V.; Ivankova, A.V.; Romanova, V.O.; Lozinsky, S.E.; Burdeina, L.V.; Savytska, O.O.; Knyazkova, I.I. (World of Medicine and Biology, 2025)
231 patients by hypertensive disease with II stages were inspected, 105 men and 126 women, the average ages of 52.3±1.2 years. Duration of arterial hypertension was the average 9.7±0.45 years. At 121 from 231 inspected patient’s ischemic heart disease – stable angina of II-III of functional class was diagnosed. Chronic heart failure of II-III FC (NYHA) was present at 90 from the inspected patients: at 39 (35.5 %) from 110 patients in a group with hypertensive disease and at 51 (42.1 %) from 121 – in the group of hypertensive disease in combination with coronary heart disease. Research purpose: estimation of deposit of coronary heart disease in the processes of remodeling and functional states of myocardium for the patients of hypertensive disease II the stages. It was set that tacking of coronary heart disease to hypertensive disease increases the degree of pathological remodeling of myocardium, mainly, due to dilatation of heart, and instrumental in progress of systole and diastolic dysfunction. Combination of hypertensive disease and coronary heart disease is instrumental in the increase of number of patients with violations of cardiac rhythm, including with ventricular extrasystoles of high gradation of Lown. Arterial hypertension and coronary heart disease make worse each another, and their combination results in the increase of cardiovascular risk.
Keywords: hypertensive disease; coronary heart disease; structurally-functional indexes of myocardium; remodeling of myocardium; systolic dysfunction; diastolic dysfunction